Can plastid genome sequencing be used for species identification in Lauraceae? - Liu, Zhi-Fang; Ma, Hui; Ci, Xiu-Qin; Li, Lang; Song, Yu; Liu, Bing; Li, Hsi-Wen; Wang, Shu-Li; Qu, Xiao-Jian; Hu, Jian-Lin; Zhang, Xiao-Yan; Conran, John G; et al. (Botanical journal of the Linnean Society, 2021)
Abstract Using DNA barcoding for species identification remains challenging for many plant groups. New sequencing approaches such as complete plastid genome sequencing may provide some increased power and practical benefits for species identification beyond standard plant DNA barcodes. We undertook a case study comparing standard DNA barcoding to plastid genome sequencing for species discrimination in the ecologically and economically important family Lauraceae, using 191 plastid genomes for 131 species from 25 genera, representing the largest plastome data set for Lauraceae to date. We found that the plastome sequences were useful in correcting some identification errors and for finding new and cryptic species. However, plastome data overall were only able to discriminate c. 60% of the species in our sample, with this representing a modest improvement from 40 to 50% discrimination success with the standard plant DNA barcodes. Beyond species discrimination, the plastid genome sequences revealed complex relationships in the family, with 12/25 genera being non-monophyletic and with extensive incongruence relative to nuclear ribosomal DNA. These results highlight that although useful for improving phylogenetic resolution in the family and providing some species-level insights, plastome sequences only partially improve species discrimination, and this reinforces the need for large-scale nuclear data to improve discrimination among closely related species.